Using Clinical Supervision to Lower EFL Teachers’ Burnout - Hamid Marashi; Mojgan Bani-Ardalani (Issues in Language Teaching, 2017)
The present study was an attempt to explore the effect of clinical supervision on EFL teachers’ level of burnout. For this purpose, a total number of 80 male and female EFL teachers within the age range of 26 and 47 who were working at a language school in Tehran participated in this study. Forty teachers in the experimental group underwent a clinical supervision program which comprised the three steps of pre-observation conference, observation, and post-observation feedback conference while the other 40 teachers who were in the control group were subjected to the conventional supervision program of the language school. The program for both groups spanned a total period of 12 weeks. Prior to the program, the Maslach Burnout Inventory questionnaire (MBI) was used to measure the level of all of the teachers’ burnout as the pretest and again at the end of study, both groups took the MBI questionnaire as the posttest. The analysis of the test scores using a test of analysis of covariance (ANCOVA) revealed that the clinical supervision program had lowered significantly the participants’ burnout. As a result of this study, the researchers suggest that ELT establishments take into consideration the practice of clinical supervision to enhance their teachers’ performance.